Canine circovirus: emergence, adaptation, and challenges for animal and public health - Silva, Diego Ferreira da; Ciola, Milene; Lopes, Verônica de Oliveira; Matias, Débora Rhayanne Medeiros; Oliveira, Tarley Santos; Castro, Alessandra Marnie Martins Gomes de (Frontiers in Veterinary Science, 2025)
IntroductionCanine circovirus (CanineCV) is an emerging pathogen with a significant impact on animal health and potential zoonotic risks. This study addresses its characterization, epidemiology, pathogenesis, and diagnostics, emphasizing its relevance within the One Health approach.BackgroundThe increasing detection of CanineCV across various species and regions highlights its genetic adaptability and cross-species transmission potential. Furthermore, growing interactions among domestic animals, wildlife, and humans amplify the need to understand its public and animal health implications.ObjectiveTo analyze the biology, epidemiology, and diagnostic challenges of CanineCV, focusing on its genetic evolution, interactions with co-infections, and implications for control strategies.MethodsA systematic literature review was conducted, synthesizing data from epidemiological, genomic, and clinical studies. Molecular techniques, such as PCR and qPCR, were evaluated for their efficacy in virus detection and quantification.ResultsCanine circovirus exhibits high genetic variability and has been detected in diverse species and tissues. Co-infections, including parvovirus and adenovirus, exacerbate clinical signs, primarily gastrointestinal, and respiratory. Advances in diagnostics, such as real-time PCR and in situ hybridization, have demonstrated increased sensitivity in viral detection.ConclusionCanine circovirus poses a growing challenge to animal health and a potential threat to public health due to its genetic plasticity and adaptability to multiple hosts. Continuous research is essential to understand its pathogenesis, develop effective control measures, and mitigate risks in diverse ecosystems.